Diagnosis of the academic performance of students of an undergraduate school in Mexico - Hernández Herrera, Claudia Alejandra (Revista Complutense de Educación, 2016)
The objective of this article is to make a diagnosis of the perception of the factors that intervene in the academic performance of students of five university degrees in a high school in Mexico, to recognize the opportunity areas that allow suggesting policies and strategies to increase their performance. A sample of 1651 students was used; the data were obtained by a thirty-question questionnaire that studies the perception of the academic performance in the Likert scale. An exploratory factorial analysis was made to reduce the data, ease the interpretation and validate the instrument. Three factors were identified: a) the role of teachers, b) the evaluation and c) students’ motivation. A comparative analysis of the different university degrees was made. It was found that students perceive that most of the teachers do not worry about the condition of youngsters in situation of reprobation with failure issues. Besides, teachers seldom motivate and lack the expressions of sentiments of pride towards students’ academic achievements. Half of the participants think that teachers do not impart the whole syllabus. Students have a high motivation, which is positive because they prove to be responsible and dedicated. In conclusion, a series of suggestions are provided while explaining the implications that this research has for undergraduate education institutions.
Keywords: academic performance; undergraduate education; students; evaluation; students’ motivation